PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN DI PT MITRA SISTEMATIKA GLOBAL - Acmad Fauzi (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Information systems are generally known as tools to facilitate the process of using data or processing within an organization, institution or business entity. Systematically, information systems are indeed used to streamline data processing in various interests, especially in the aspect of decision making. In addition, the information system has several functions including collecting and entering data, storing data, and producing information output. PT. Global Systematic Partners are currently still not optimally using information systems, especially attendance.